Pelatihan Pembuatan Dan Pengelolaan Website Di SMKN 2 Lumajang - Faozen, Faozen; Juhanda, Juhanda; Siswanto, Edhi (Universitas Muhammadiyah Jember, 2023)
This PKM aims to overcome the problems of the State High School (SMK) 2 Lumajang in the management and utilization of the website in the KBM and information process. The problems encountered by the State High School (SMK) 2 Lumajang include (1) Information technology that is already widely available in schools has not been utilized optimally as a medium to support the teaching and learning process and school information, (2) The ability of teachers / website admins who are still minimal in utilizing information technology as a medium to support the teaching and learning process and school information, (3) The web is a media that is currently popular among the younger generation and has facilities that can be used as a medium to support the teaching and learning process and school information, (4) The demands of the times that have been increasingly advanced in information technology. The solutions offered are (1) Providing skills and abilities to create and manage websites as a supporting medium for the teaching and learning process and school information (2) Information technology in this case the Internet network available in schools can be utilized optimally as a medium to support the teaching and learning process and school information; (3) Develop Training Modules (4) Partner assistance (4) Website Creation Simulation and its management. The external target to be achieved is skills in the use of information technology for teachers and school web admins by creating and managing a website as a medium to support the teaching and learning process and school information and improving the ability of teachers to utilize information technology to create and manage teacher websites and school websites.